Factors contributing to the performance of the Roads Agency Limpopo in terms of roads infrastructure delivery - Rapetsoa, Molatelo (My University, 2011)
The overall aim of the study was to investigate the factors contributing to RAL’s performance on roads infrastructure delivery in Limpopo Province for the first ten years since its inception. The study also sought to assess RAL’s steadiness, looking at its current practices and processes versus key external and internal developmental challenges facing the construction industry, in particular the civil engineering profession. Descriptive explorative research design using an instrumental case study was used in this research project to achieve the aim of the study. The population comprised all the people and companies involved with the RAL projects in Limpopo Province, including RAL staff, CIBD active registered Civil Engineering Contracting and consulting firms. Unstructured telephonic interviews and a structured questionnaire assisted the researcher to understand factors contributing to RAL’s performance in roads. The study revealed several strengths and weaknesses contributing to RAL’s performance, which concerned the agency‘s nature and composition, level of implementation of its strategies, policies and plans. A clear and implementable quality assurance system must be developed to mitigate all risks associated with project management processes and procedures. Strategies should also be identified on how the agency’s performance will progress despite the economic instability and political interferences. Proper strategic planning has thus far proved to be prudent in identifying risks and ways to mitigate them. According to the study RAL, an organisation of its own type specialising in roads infrastructure, its nature and size, its vast experience and knowledge of construction and project organisation and Project managers’ experience, competence and commitment to finishing the project with time ,cost and budget, have emerged as key ingredients assisting it in becoming an organisation with its proven record. The study also demonstrated RAL’s strength in terms of its communication, control and dedication in managing projects. However too many tenders are issued within a short space of time which makes contractors unable to adequately respond to them. RAL has demonstrated that it is negatively affected by an unstable economic environment. As a result construction materials are always aligned to inflation. To that end RAL should constantly monitor market conditions to synchronize its activities to 5 rightfully position themselves as these are external factors that are unavoidable, but require a hands-on approach
Thesis (M.Dev.) --University of Limpopo, 2011
Keywords: Performance measurement; Organizational effectiveness; Performance standards; Performance -- Evaluation; Organizational effectiveness; Employees, Rating of